Theoretical construction of the microteaching model-based PjBL and blended learning for prospective biology teachers - Ali Sadikin; Muhammad Rusdi; Muhammad Haris Effendi Hasibuan; Jodion Siburian (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
Microteaching as a learning model must be updated for the future, especially in preparing prospective biology teachers with the 4C skills required in the 21st century. This study aims to develop a microteaching model-based Project-based Learning (PjBL) and blended learning to enhance the 4C skills of prospective biology teachers. The research method uses a Research & Development approach with the ADDIE framework. The research subjects are the Biology Education Study Program students who take the microteaching course. This model integrates PjBL and blended learning, including the following stages: (1) Project orientation (synchronous), (2) Module development (asynchronous), (3) Peer review (asynchronous), (4) Presentation of peer review results (synchronous), (5) First teaching practice and peer review (asynchronous), (6) Presentation of first teaching practice results (synchronous), (7) Second teaching practice and peer review (asynchronous), (8) Presentation of second teaching practice results (synchronous), (9) Collection of project videos (synchronous), and (10) Project evaluation (synchronous). Data collection techniques include questionnaires, validation sheets, observation sheets, and tests, with data analysis using a t-test. The results show that model enhances the 4C skills of prospective biology teachers. In conclusion, this model effectively improves 4C skills with the guidance of a logbook and LMS. Still, lecturers must encourage and facilitate student learning activities through direct communication or instant messaging. This research impacts the quality of education for prospective biology teachers in the future.Abstrak. Microteaching sebagai model pembelajaran perlu diperbaharui untuk masa depan, khususnya dalam menyiapkan calon guru biologi dengan keterampilan 4C yang dibutuhkan pada abad 21. Penelitian ini bertujuan mengembangkan model microteaching berbasis project-based learning (PjBL) dan blended learning bagi calon guru biologi. Metode penelitian ini menggunakan pendekatan Research & Development dengan kerangka ADDIE. Subjek penelitian adalah mahasiswa Program Studi Pendidikan Biologi yang mengambil mata kuliah microteaching. Model microteaching yang dikembangkan mengintegrasikan PjBL dan blended learning, meliputi tahapan: (1) Orientasi proyek (sinkronus), (2) Pengembangan modul (asinkronus), (3) Peer review (asinkronus), (4) Presentasi hasil peer review (sinkronus), (5) Praktik mengajar pertama dan peer review (asinkronus), (6) Presentasi hasil praktik mengajar pertama (sinkronus), (7) Praktik mengajar kedua dan peer review (asinkronus), (8) Presentasi hasil praktik mengajar kedua (sinkronus), (9) Pengumpulan video proyek pembelajaran (sinkronus), dan (10) Evaluasi dan penilaian proyek (sinkronus). Teknik pengumpulan data menggunakan angket, lembar validasi, lembar observasi, dan tes. Teknik analisis data menggunakan t-test. Hasil menunjukkan bahwa model ini meningkatkan keterampilan 4C pada calon guru biologi. Kesimpulannya, moel ini efektif meningkatkan keterampilan 4C dengan panduan logbook dan LMS, Namun, dosen perlu mendorong dan menfasilitasi kegiatan belajar mahasiswa melalui komunikasi langsung atau pesan instan. Penelitian ini berdampak pada peningkatan kualitas pendidikan calon guru biologi di masa depan.